2016
DOI: 10.4238/gmr.15027191
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-4-dependence of the lipopolysaccharide-mediated inhibition of osteoblast differentiation

Abstract: pathogenic factor affecting bone fracture healing. Therefore, the effect of LPS on bone metabolism is relevant for bone healing. In this study, we investigated the effect of LPS on the expression of Toll-like receptor (TLR)-4 (an LPS receptor) by using real-time quantitative PCR and western blotting. We also examined the regulatory role of LPS in osteoblast differentiation by measuring the ALP activity, matrix mineralization, and ALP, OCN, and Runx2 mRNA (essential factors affecting osteoblast differentiation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This was also observed in mouse MSCs where TLR4 activation also up-regulated its own expression ( Huang et al, 2014 ). Moreover TLR4 activation in the mouse osteoblastic cell line MC3T3-E1 induced its own expression ( Liu et al, 2016 ). These apparent divergent results regarding TLR4 expression upon its stimulation might be explained according to different incubation times, agonist concentration, as well as cell-specific TLR4 expression rates.…”
Section: Tlr4 Expression In the Bone Compartmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also observed in mouse MSCs where TLR4 activation also up-regulated its own expression ( Huang et al, 2014 ). Moreover TLR4 activation in the mouse osteoblastic cell line MC3T3-E1 induced its own expression ( Liu et al, 2016 ). These apparent divergent results regarding TLR4 expression upon its stimulation might be explained according to different incubation times, agonist concentration, as well as cell-specific TLR4 expression rates.…”
Section: Tlr4 Expression In the Bone Compartmentmentioning
confidence: 99%
“…This was consistent with other reports about TRIF-independent inflammatory responses elicited by TLR4 activation in mouse osteoblasts ( Sato et al, 2004 ). According to the TLR4-mediated inhibition of certain anabolic processes, TLR4 activation in differentiating mouse primary osteoblasts ( Bandow et al, 2010 ), mouse osteoblastic cell line MC3T3-E1 ( Liu et al, 2016 ), or in mouse MSCs ( Chen et al, 2014 ) inhibited the matrix mineralization ( Bandow et al, 2010 ), whereas this activation did not inhibit the matrix mineralization of mouse MyD88 -/- -derived primary osteoblasts ( Bandow et al, 2010 ). Moreover, unlike occurred in MyD88 -/- osteoblasts, TLR4 activation of wild type osteoblasts up-regulated the mRNA of the activating transcription factor 4 (ATF4), as well as down-regulated osteoblastic transcription factors like the runt related transcription factor 2 (Runx2), and osterix (Sp7) ( Bandow et al, 2010 ).…”
Section: Tlr4 Effect On Osteoblast Differentiation and Metabolismmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) derived from Porphyromonas gingivalis (Pg), a major pathogenic component, affects bone metabolisms and aggravates periodontitis. Liu et al have recently reported that bacterial LPS inhibits osteoblastic differentiation and alkaline phosphatase (ALP) activity by suppressing the expressions of osteocalcin, Runx2, and ALP, and then downregulates bone matrix mineralization [10]. Moreover, LPS induces inflammatory cytokine levels, such as IL-1β, IL-6, IL-8, TNF-α, and S100A8/S100A9 from various cells in periodontal tissues [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, all positive cells share the basic traits of this pathway such as responsiveness to LPS reflected by activation of transcription factors of the NF-κB family and production of inflammatory cytokines. During inflammation, TLR4-expressing normal cells significantly increase secretion of inflammatory mediators [25,30] due to co-upregulated TLR4 [31], its intracellular adapters [32], and co-receptors [10] which enhances cooperation among the pathway's components. Likewise, malignant TLR4-positive cells express much higher levels of inflammatory proteins as compared with their normal counterparts [33,34].…”
Section: Tlr4 Expression In Normal Organsmentioning
confidence: 99%
“…Macrophages are natural responders to TLR4 ligands having the highest expression of this receptor. Under inflammatory conditions, TLR4 is further upregulated by LPS [31] and cytokines [195] through positive feedback loops. Tumor-associated macrophages (TAMs) are well-known promoters of metastasis through secretion of growth-promoting cytokines, proteases [196], and immunosuppressive factors [197].…”
Section: Indirect Pro-oncogenic Effects Of Tlr4 Mediated By Cells In mentioning
confidence: 99%